Learning styles of Yemeni undergraduate science students - Angela Abu-Asba; Hazita Azman; Rosniah Mustaffa (Penerbit UKM, 2012)
The aim of this paper is to investigate the preferred learning styles of 179 Yemeni students studying science at the Faculty of Science, Sana’a University, Yemen in response to a need for improving the learning of science among Yemeni students. A learning style refers to the ways of learning that include how learners perceive, interact with and respond to the learning environment. This paper applies Reid’s (1995) taxonomy of six learning style preferences: visual, auditory, kinesthetic, tactile, group, and individual styles to classify the styles of the students in this study. Data was collected through questionnaires, interviews, observation checklists, and field notes. The questionnaire data was coded and analyzed using the SPSS program while the interview data was transcribed, organized, coded, categorized, and analyzed. The findings show that the tactile and kinesthetic styles were the most prevalent styles among the students, followed by the auditory style. This has pedagogical implications for the teaching of science in Yemen.